Faktor-Faktor yang Berhubungan dengan Kejadian Tuberkulosis di Kecamatan Nisam, Kabupaten Aceh Utar - Dian Rahayu; Elly Safwani; Intan Rizqi; Khairuman Khairuman (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
Tuberculosis is one of the dangerous infectious diseases and is still a public health problem in Indonesia. Nisam District is one of the sub-districts in North Aceh with the highest TB cases in 2024, This study aims to analyze factors related to the incidence of tuberculosis (TB) in Nisam District, North Aceh Regency. The research design used was cross-sectional. The population in this study is all people living in Nisam District, and the sampling in this study used purposive sampling as many as 30 respondents. The results of the study found a relationship between sex (p: 0.002, OR: 55.00, CI: 4.13-732.71), knowledge (p: 0.005, OR: 35.00, CI: 2.98-411.47), behavior (p: 0.023, OR: 15.00, CI: 1.45-155.31), occupancy density (p: 0.002, OR: 115.00, CI: 6.11-2165.95) and floor type (p: 0.013, OR: 14.00, CI: 1.74-112.55) against the incidence of TB. So it is suggested to the Health Office through Promkes that it is expected to increase education on TB prevention based on gender, knowledge, and environmental conditions, while Puskesmas, especially surveillance personnel and TB programs, need to optimize active screening, patient coaching, and cadre empowerment, and the community is encouraged to create healthy housing and increase awareness of TB.